Relationships between climate change and periglacial environment at Col d’Olen site (NW Italian Alps) - COLOMBO, NICOLA; FRATIANNI, SIMONA; GARZENA, DIEGO; GODONE, DANILO FRANCESCO; GUENZI, DIEGO; Elisa, Giaccone; Elena, Serra (SISC, 2015)
The high altitude areas are characterized by periglacial environment, very sensible to climate change. At Col d’Olen site, situated in NW Italian Alps, a pilot study started in rock glacier, which front is located at 2710 m a.s.l. The aim of this project is understand the impact of climate-ground parameters on alpine permafrost. For this reason, in the rock glacier surface, 70 iButton®dataloggers have been installed at 5/10 cm into the ground to monitor the ground temperature every three hours. A preliminary download has been carried out at the end of August 2015, allowing to achieve a complete year of data (starting in July 2014). The dataset has been analyzed to individuate the potential distribution of permafrost and to know the temperature variations throughout the year. To know the climate of study area, the data of Col d’Olen meteorological station, located near to the Institute Mosso (2900 m, Long Term Ecological Research site), has been analyzed, together with those of five meteorological stations situated in neighboring; the climatic indices of ETCCDMI and the trends of principal climatic parameters (temperature, precipitations and snow) have been calculated for the six stations. To better analyze the climate of study area, in July 2014 a portable automatic weather station has been installed in front of the rock glacier to collect a more punctual climatic information, which will be extend the data of Col d’Olen meteorological station. Furthermore, the climate data of last year (2014-2015) of Col d’Olen station have been related to rock glacier ground temperature data to look for a correlation between atmosphere and cryosphere.